Mulk Raj Anand’s Novel Based on Themes, Social Realism and Societal Values: Exploring Social Realism and Exploitation in Mulk Raj Anand's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mulk Raj Anand is extremely outstanding as an Indian novelist, recognized essayist, reformer, craftsmanship commentator, editorial manager, columnist, a short story author and political lobbyist. He opened another area of scholars of fiction alongside Raja Rao and R. K. Narayan and created a lot of English literature and his dominance in the reasonable and thoughtful depiction of the misused class of Indian society denotes his virtuoso as a socially dedicated novelist. Painted with the colors of social realism Mulk Raj Anand‟s two novels Untouchable and Coolie mirror the in-your-face reality of the Indian society of early many years of twentieth century.Composed with a reason both these novels censure the cutting edge free enterprise Indian society and medieval framework for the bold and lamentable exploitation of poor people and underdog as there is only a genuine, genuine and unpleasant impression of the society in both the novels managing a comparable focal topic of social exploitation, the exploitation of the discouraged and the under-special on account of the scourge of untouchability, poverty, hunger, child work, social governance, social set up of society, traditions, religious conviction, preferences and the suffering of the Indian masses by the powers of private enterprise, industrialism and expansionism. The present examination demonstrates the real nature of social realism in Untouchable and Coolie the epic like novels of M. K. Anand to strike a string in the hearts of the consciententious Indians through an excellent and genuine to life depiction of the abused masses of Indian society.